Exploring Environmental Consciousness and Human Connection in the Overstory - Geeta,; Dr. Savita Andelwar, (International Journal of Scientific Research in Science and Technology, 2024)
This paper critically examines the novel written by Richard Powers which is divided into four parts: Roots, Trunks, Crown, and Seeds. It examines the relationship between humans and forests and highlights environmental ethics. The book tells the story of nine Americans who, through their diverse life experiences with trees, come together to confront the issue of forest degradation. The study employs qualitative methods and theoretical analyses to illuminate the interdependence of humankind and the natural world. This study uses an eco-critical perspective to contribute to ongoing discussions about environmental stewardship and the urgent need for harmonious living with nature. It aims to raise consciousness about ecological problems among humans. Eventually, it seeks to plant the seeds of environmental consciousness. It shows that literature plays a crucial role in educating people about these issues and inspiring them to take action to protect the environment.
Keywords: Ecocriticism; Environmental Consciousness; Forest; Tree; Awareness